Tom Dooley, Jungle doctor: a story about Dr. Thomas A. Dooley - Hugh, Alice (Minneapolis, MN : Winston press, 1979)
Briefly focuses on the American physician's work with orphans in southeast Asia.
Keywords: Missionaries, Medical-- Southeast Asia--Biography -- Juvenile literature